Optimization of Microcrystalline Cellulose from Bagasse (Saccharum officinarum) by Acid Hydrolysis - Prayoga, Wahyu Nur Alfath; Aziz, Adit Abdul; Syahrir, Adam; Pitaloka, Alia Badra (World Chemical Engineering Journal, 2023)
Microcrystalline cellulose (MCC) is a compound produced from refining alpha cellulose with excessive amounts of acidic minerals that has a white visual color, odorless and biodegradable. MCC is often used as an excipient in the pharmaceutical and food industries. This study aimed to determine the content of alpha cellulose from bagasse with varying concentrations of nitric acid and the highest degree of crystallinity produced from microcrystalline cellulose. The research began with drying and smoothing bagasse. Then, the bagasse was delignified using HNO3 solution with a concentration of 5%, 7.5% and 10%, followed by NaOH solution. The sample obtained was bleached using NaClO solution to obtain alpha cellulose. Then, alpha cellulose was hydrolyzed using HCl solution to obtain microcrystalline cellulose. The purity of alpha cellulose with nitric acid concentrations of 5%, 7.5%, and 10% was 37.63%, 32.48%, and 23.73%, respectively, and the highest crystallinity produced was 67.45% in MCC HNO3 10%.